Biodegradation of naphthalene by bacteria isolated from Port Dickson coastal waters - Ng Siew Theng (Terengganu: Kolej Universiti Terengganu, 2014)
A naphthalene degrading bacteria was isolated from the coastal waters of Port Dickson and was named Nap C in this study. The optimum growth condition for Nap C was at the temperature of 30°C, salinity of 30 ppt and pH 8.